(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
The article discusses the need to develop students’ literacy in oral and written texts in the state language, to create meaning in our language - to feel the primary feature, to understand that the future is the basis of a noble word in the development of all spheres of society. Teachers will also be given some tips to strengthen students’ spelling skills.